Surface segregation and chromium deposition and poisoning on La 0.6Sr0.4Co0.2Fe0.8O 3-d cathodes of solid oxide fuel cells - Zhao, L.; Drennan, J.; Kong, C.; Amarasinghe, S.; Jiang, San Ping (Electrochemical Society Inc., 2013)
La0.6Sr0.4Co0.2Fe0.8O 3-d, (LSCF) perovskite oxide is one of the most common cathode materials used in solid oxide fuel cells (IT-SOFCs), but vulnerable to the chromium deposition and poisoning in the presence of gaseous chromium species from metallic interconnect. In this work, the fundamental relationship between the surface segregation and Cr deposition and poisoning of LSCF cathodes is studied on dense LSCF bar samples. The detailed SEM and FIB-EDS analysis results clearly indicate the segregation of strontium and cobalt, forming individual SrO and CoOx particles on the LSCF surface after annealing at 800 °C for 96 h. The results indicate that Cr deposition occurs preferentially on the segregated SrO particles on the LSCF surface. © The Electrochemical Society.